Disk-ring deposition in drying a sessile nanofluid droplet with enhanced marangoni effect and particle surface adsorption - Ren, Junheng (2022)
The present study is to explore the central particle deposition from drying a sessile nanofluid droplet experimentally and theoretically. Normally, a pinned colloidal droplet dries into a coffee-ring pattern as a result of moving the particles to a three-phase line by the radial direction capillary flow. However, the strong evaporation can generate the nonuniform temperature at the evaporating droplet interface and the droplet periphery temperature is higher than that close to the droplet centerline. The induced Marangoni flow would reversibly transport the particles at the periphery toward the centerline. We have thus designed the experiments to increase the droplet evaporation rate in vacuum conditions and accordingly to enhance the Marangoni effect. We have observed distinguishable disk deposition inside the outer coffee ring. A three-dimensional diffusion-limited cluster-cluster aggregation Monte Carlo model has been developed to simulate the deposition process. With modeling the Marangoni effect, particle adsorption at the liquid-air interface and particle aggregation behaviors, the formation of the disk pattern inside a coffee ring has been simulated. The qualitative agreement has been found in the comparison of local deposition distribution between the related experiment and simulation.